Study on plastic and mechanical properties of plastic stabilized returned plastic concretes containing supplementary cementitious materials - Mali, Sarvesh (Curtin University, 2016)
The growing concern for ready mix concrete industry is the disposal of returned unused concrete. In a plastic state, the concrete is a perishable product and the disposal of any unused concrete provides a set of challenges. However, little is known about the most effective parameters for recycling of returned plastic concrete without adversely affecting its properties. The present research has conducted laboratory trials to establish an optimal process for stabilizing returned plastic concretes using set-retarding admixture called “stabilizer”. Three types of cements, widely used in construction industry in Australia, are used in this research. The first is the ordinary Portland cement (OPC), while the rest are blended cements containing 25% class F fly ash and 65% slag as partial replacement of OPC.